The larvae of Chinese Hydropsychidae (Insecta: Trichoptera), Part II: Potamyia chinensis and Cheumatopsyche trifascia - Zhang, Ao; Zhou, Xin (Zootaxa, 2021)
The larvae of Chinese caddisflies Potamyia chinensis and Cheumatopsyche trifascia were successfully associated with identifiable adults using independent DNA markers, mitochondrial COI barcodes and nuclear ribosomal 28S D2 genes. A total of 49 specimens collected in China were employed in the molecular analyses. The two markers were congruent on species boundaries for 11 distinctive haplogroups, while D2 failed in differentiating two closely related species. A brief summary for larval studies of both genera is given, followed by an introduction to the generic morphological characteristics, and detailed morphological descriptions and illustrations for the two successfully associated species. The larva of P. chinensis is re-described here based on Chinese materials, following the previous larval description for P. echigoensis, which was recently synonymized with P. chinensis.